2020
DOI: 10.3390/cells9071744
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics-Based Transplacental Delivery as a Useful Noninvasive Tool for Manipulating Fetal Genome

Abstract: We previously demonstrated that the injection of pregnant wild-type female mice (carrying enhanced green fluorescent protein (EGFP)-expressing transgenic fetuses) at embryonic day (E) 12.5 with an all-in-one plasmid conferring the expression of both Cas9 and guide RNA (targeted to the EGFP cDNA) complexed with the gene delivery reagent, resulted in some fetuses exhibiting reduced fluorescence in their hearts and gene insertion/deletion (indel) mutations. In this study, we examined whether the endogenous myosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Mice [1,2,12] and rats [12,19] are the animals most commonly used for systemic injection from the tail vein; treeshrews are systemically injected using the retro-orbital sinus [20], and chickens using the jugular vein [21]. The liver is the primary organ affected by systemic injection, but substantial transgene expression has also been confirmed in other organs, such as the kidneys [21], brain capillary endothelial cells [22], and even extraordinary tissues, such as subcutaneously implanted colorectal cancer cells [23,24] and fetuses in pregnant animals [25].…”
Section: Target Animals Organs and Routes Of Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice [1,2,12] and rats [12,19] are the animals most commonly used for systemic injection from the tail vein; treeshrews are systemically injected using the retro-orbital sinus [20], and chickens using the jugular vein [21]. The liver is the primary organ affected by systemic injection, but substantial transgene expression has also been confirmed in other organs, such as the kidneys [21], brain capillary endothelial cells [22], and even extraordinary tissues, such as subcutaneously implanted colorectal cancer cells [23,24] and fetuses in pregnant animals [25].…”
Section: Target Animals Organs and Routes Of Injectionmentioning
confidence: 99%
“…The epoch-making discovery and establishment of the CRISPR (clustered regularly interspaced short palindromic repeats)-Cas9 system are rapidly progressing toward use in in vivo gene editing. Hydrodynamic delivery plays a key role in delivering the components required for in vivo site-directed gene editing, not only for CRISPR-Cas9 [25,95,203,218,219] but also for other systems, such as prime editors [141], split prime editors [140], adenosine deaminase acting on RNA [226], and adenine base editors [139].…”
Section: Delivery Materials Technological Developments Gene Editingmentioning
confidence: 99%
“…Nakamura et al [84] extended TPGD-GEF and showed that HGD of plasmid pCGSap1-MHC (targeted to endogenous myosin heavy chain α (MHCα) gene) in pregnant females on E9.5 resulted in the generation of genome-edited fetuses with an efficiency of 4.16% (Figure 2). Molecular analysis revealed that the mode of genome editing seen in these fetuses was mosaic (i.e., a mixture of genome-edited and non-genome edited cells).…”
Section: Targeted To Fetal Livermentioning
confidence: 99%
“…Hydrodynamics-based gene delivery (HGD)-based transplacental gene delivery for acquiring genome-edited fetuses (TPGD-GEF) using all-in-one vector pCGSap1-MHCα [84]. First, B6C3F1 females were mated to C57BL/6 male mice.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation